(untitled) (Research, Society and Development, 2021)
The investigation of quality of life related to professional health becomes relevant and may reflect on the health of the nursing professional and thus impact on their health-related quality of life. Objective: to analyze the health profile and health-related quality of life of mid-level nursing agents from old age onwards. Method: Cross-sectional study with a quantitative approach, with mid-level nursing agents in the third age, with application of a semi-structured script in addition to the instrument The Medical Outcomes Study 36-item Short-Form Health Survey (SF-36), during the second semester of 2019. The collected data were organized and tabulated using the absolute (n) and relative (%) frequency and presented in tables, in addition to the Shapiro-Wilk test to verify the normality of the data and then proceeded with the non-test. parametric for Kruskal-Wallis medians, which when significant (p<0.05), the Conover-Iman test was used for multiple comparisons between the medians. Results: factors such as obesity, sedentary lifestyle, physical limitations, chronic and occupational diseases, overload and strain from work were identified as aggravating the health and quality of life of professionals. With the application of the SF-36 instrument, it was observed that the social aspects domain had a better mean score, and the general health domain had a lower mean score. Conclusion: Furthermore, it is concluded that nursing still lacks better conditions in their work activities and new strategies for coping with illness in nursing.